Environmental compliance - Jones, H. (Mine Waste 2010: Proceedings of the First International Seminar on the Reduction of Risk in the Management of Tailings and Mine Waste, 2010)
The Macquarie dictionary defines ‘compliance’ as ‘1. An act of conforming; acquiescing, or yielding. 2. base subservience.’ Does environmental compliance mean yielding to environmental forces, or does it mean being subservient to a human perception of the environment? How ‘environmental compliance’ may be defined by the various stakeholders in the mining industry, companies, governments and communities is considered in the light of their possible objectives in requiring ‘environmental compliance’. Examples of potentially conflicting environmental requirements in waste management are considered, particularly operational requirements such as minimal dust generation versus completion environmental compliance requirements of establishing a self-sustaining ecosystem or geomorphologically stable landform. Mechanisms available to establish standards for determining if environmental compliance has been attained are described. These include guidelines (company and government), which can range from detailed (tailings construction) to broad and general (closure strategies); codes of practice, Ministerial conditions and regulations are discussed. Some of the strengths and weaknesses these mechanisms are described, using examples from industry experience. The site specific nature of most mine waste management operations means that one approach cannot fit all situations and the fairness of having a solution acceptable in one operation, but not in another is discussed. Does strict compliance with a human perception of the environment and how it functions promote a ‘lowest common denominator’ approach? The potential technology restricting aspects of requiring ‘compliance’ is discussed and the alternative compliance requirements of ‘‘outcome’ compliance and ‘process’ compliance considered. The time frame for assessing environmental compliance is discussed. The potential use of simulation models as potential tools for assessing future environmental performance is considered. Moreover, it is concluded that ‘environmental compliance’ means conforming to the environment rather than simply acquiescing or yielding to man-made ‘rules’.